Fair Fault-Tolerant Approach for Access Point Failures in Networked Control System Greenhouses - Ba Humaish, Mohammed Ali Yaslam (AUC Knowledge Fountain, 2024)
Greenhouse Networked Control Systems (NCS) are popular applications in modern agriculture due to their ability to monitor and control various environmental factors that can affect crop growth and quality. However, designing and operating a greenhouse in the context of NCS could be challenging due to the need for highly available and cost-efficient systems. This thesis presents a design methodology for greenhouse NCS that addresses these challenges, offering a framework to optimize crop productivity, minimize costs, and improve system availability and reliability. It contributes several innovations to the field of greenhouse NCS design. For example, it recommends using the 2.4GHz frequency band instead of 5GHz to minimize Access Point (AP) costs while maintaining an acceptable Packet Loss Rate (PLR) of ≤ 2%, and prolonging sensor battery life by reducing transmission power. Additionally, it proposes a metric, Ψ, to help management select an architecture that minimizes crop profit loss, considering factors like AP failure and repair rates, and overall greenhouse efficiency. Markov models are used to calculate steady-state availability (AVss) and determine system downtime. System availability is assessed by modeling various architectures using SHARPE. Moreover, the Quality of Experience (QoE) metric is used to enhance the selection process of optimal distributions in the event of single, double, and triple AP failures. QoE serves as a valuable tool for system designers to evaluate and compare different distribution strategies, taking into account factors such as packet loss rates, latency, and user perception. This metric enables informed decision-making in selecting the most suitable distribution strategy, ensuring robust and efficient operations of greenhouse NCS, even under challenging conditions. The simulation tool, Riverbed Modeler, is used to evaluate greenhouse NCS operation in terms of PLRs. The methodology and contributions of this thesis were validated through a case study on a greenhouse NCS found in the literature. The results show that the methodology can significantly reduce costs while maintaining an acceptable level of system reliability and performance. These contributions provide a comprehensive design methodology for greenhouse NCS, applicable to farmers and greenhouse operators, aimed at improving the quality and profitability of their yield.